SOLAR POWERED EV CHARGER USING RFID (International Journal of Engineering Management Science, 2024)
There are many uses for wireless technology in both residential and commercial contexts. The primary objective is to use resonant inductive coupling to transfer power wirelessly between the transmitting and receiving coils in the near field. As a result, we developed a wireless solar-powered bicycle charging station. In order to confirm optimal charging, which reduces energy losses, high efficiency is necessary. The bikes are individually scanned by the RFID tag technology, which allows charging in locations where unauthorised users have been forewarned or prohibited. Mobile apps are often used to monitor and control this. For electric cycles, having a flexible wireless charging station is particularly important to accomplish wireless power transfer via inductive coupling. Reducing infrastructure costs and increasing portability and mobility require a charging station.
Keywords: Cyber security, Electric vehicles,RFID,Electric vehicle charging stations, Smart grids